First determination of azole resistance in Aspergillus fumigatus strains carrying the TR34/L98H mutations in Turkey. Issue 8 (August 2015) - Özmerdiven, Gülşah Ece; Ak, Seçil; Ener, Beyza; Ağca, Harun; Cilo, Burcu Dalyan; Tunca, Berrin; Akalın, Halis
Abstract Aspergillus fumigatus is the most important etiological agent of invasive aspergillosis. Recently, an increasing number of azole-resistant A. fumigatus isolates have been described in various countries. The prevalence of azole resistance was investigated in this study using our culture collection of A. fumigatus isolates collected between 1999 and 2012 from clinical specimens. Seven hundred and forty-six A. fumigatus isolates, collected from 419 patients, were investigated. First, all isolates were screened for resistance to itraconazole by subculturing on Sabouraud dextrose agar that contained 4 mg/L itraconazole. For isolates that grew on the itraconazole containing agar, the in vitro activities of amphotericin B, itraconazole, voriconazole and posaconazole were determined using the Clinical and Laboratory Standards Institute (CLSI) M38-A reference method. After PCR amplification, the full sequence of the cyp51A gene and its promoter region was determined for all in vitro azole-resistant isolates. Itraconazole resistance was found in 10.2% of the A. fumigatus isolates. From 2000 onwards, patients were observed annually with an itraconazole-resistant isolate. According to in vitro susceptibility tests, amphotericin B exhibited good activity against all isolates whereas the azoles were resistant. Sequence analysis of the promoter region and CYP51A gene indicated the presence of TR34/L98H in 86.8% (n = 66) of isolates. This initial analysis of the resistance mechanism of A. fumigatus from Turkey revealed a common TR34/L98H mutation in the cyp51A gene.